Greater soil water and nitrogen availability increase C : N ratios of root exudates in a temperate steppe. (October 2021) - Li, Chao; Liu, Lu; Zheng, Lang; Yu, Yang; Mushinski, Ryan M.; Zhou, Yong; Xiao, Chunwang
Abstract: A better understanding of how rates and stoichiometric signatures of root exudates respond to altered N deposition and rainfall patterns is critical for predicting future impacts of environmental changes on ecosystem function and services. Here, we conducted a field experiment examining the effects of rainfall reduction (−50% compared to the control with normal rainfall), rainfall addition (+50%), N addition (~10 g N m −2 yr −1 ), and their interactions on root C and N exudation rates and C : N ratios of root exudates from dominant species in a temperate steppe. We hypothesized that increasing soil water and N availability will increase C: N ratios of root exudates because plants will grow more and retain more N in their biomass, thus have lower root N exudation rates. We found greater changes in root N exudation rates (ranging from −18% ~ +11%) than C exudation rates (ranging from −6 ~ +11%) in response to rainfall and N treatments. In addition, N addition and its interactions with rainfall treatments decreased root N exudation rates by 4–18% and therefore increased C : N ratios of root exudates by 8–27% compared to control; however, a contrasting pattern was found under rainfall reduction. Furthermore, changes in root C exudation rates in response to rainfall and N treatments were not related to changes in plant biomass. In contrast, root N exudation rates decreased with increasing plant biomass, resulting in an overall increase in C : N ratios of root exudates with increasing plant biomass. Overall, our results reveal the C : N stoichiometric plasticity of root exudates in response to resource modifications. These findings have important implications for understanding rhizosphere plant-soil-microbe interactions and ecosystem functioning under environmental changes. Highlights: Root N exudation rates are responsive to changes in soil resources. C: N ratios of root exudates are sensitive to altered rainfall and N patterns. Root N exudation rates decrease with increasing plant biomass.